2022
DOI: 10.1039/d2an00694d
|View full text |Cite
|
Sign up to set email alerts
|

Construction of dPCR and qPCR integrated system based on commercially available low-cost hardware

Abstract: Fluorescent quantitative PCR (qPCR) and digital PCR (dPCR) are two mainstream nucleic acid quantification technologies. However, commercial dPCR and qPCR in-struments have a low integration, a high price, and a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As for ultra-sensitive quantification of DNA at lower concentrations (dozens of copies or even a single copy), studies have shown that ordinary fluorescence PCR is inherently unreliable, so the digital PCR method was specially invented to meet the needs of absolute quantification, making up for the inadequacy of real-time PCR. 22,52 Comparative analysis and outlook…”
Section: Comprehensive Characterization Of the Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…As for ultra-sensitive quantification of DNA at lower concentrations (dozens of copies or even a single copy), studies have shown that ordinary fluorescence PCR is inherently unreliable, so the digital PCR method was specially invented to meet the needs of absolute quantification, making up for the inadequacy of real-time PCR. 22,52 Comparative analysis and outlook…”
Section: Comprehensive Characterization Of the Systemmentioning
confidence: 99%
“…28 Therefore, an affordable smartphone imaging device can obtain the fluorescence intensities of all cycles for sensitive and timely DNA analysis, which is superior to qualitative electrophoresis and dedicated multi-fiber detection or multi-zone fluorescence imaging. 22,29,30 As a proof of concept, we built a 3-D printed prototype and evaluated the performance including nucleic acid extraction efficiency and quantification ability with hepatitis B virus DNA (HBV-DNA) spiked plasma samples. The results show that this study can complete 69% DNA extraction from a 100-μL plasma sample within 14 minutes, and achieve real-time fluorescence amplification of a 40-μL PCR reagent within 23 minutes, with a quantitative range of up to 6 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of novel coronavirus is an important part of controlling the epidemic. Therefore, it is imperative to develop a test instrument that is easy to operate and quick to measure [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%